Investigation of catechin’s anti-inflammatory activity: A bioinformatics and molecular docking study - Nisa Yulianti Suprahman; Bulan Rosita Sari; Riri Fauziyya; Fatimah (Acta Biochimica Indonesiana)
Background: Inflammation plays a key role in the progression of many chronic diseases. As a country with rich biodiversity, Indonesia offers numerous phytochemicals with potential for drug development, including catechin, a natural compound with anti-inflammatory properties.